Design, synthesis and docking study of novel coumarin ligands as potential selective acetylcholinesterase inhibitors - Fatih Sonmez; Belma Zengin Kurt; Isil Gazioglu; Livia Basile; Aydan Dag; Valentina Cappello; Tiziana Ginex; Mustafa Kucukislamoglu; Salvatore Guccione (Taylor & Francis Group, 2017)
New coumaryl-thiazole derivatives with the acetamide moiety as a linker between the alkyl chains and/or the heterocycle nucleus were synthesized and in vitro tested as acetylcholinesterase (AChE) inhibitors. 2-(diethylamino)-N-(4-(2-oxo-2H-chromen-3-yl)thiazol-2-yl)acetamide (6c, IC50 value of 43 nM) was the best AChE inhibitor with a selectivity index of 4151.16 over BuChE. Kinetic study of AChE inhibition revealed that 6c was a mixed-type inhibitor. Moreover, the result of H4IIE hepatoma cell toxicity assay for 6c showed negligible cell death. Molecular docking studies were also carried out to clarify the inhibition mode of the more active compounds. Best pose of compound 6c is positioned into the active site with the coumarin ring wedged between the residues of the CAS and catalytic triad of AChE. In addition, the coumarin ring is anchored into the gorge of the enzyme by H-bond with Tyr130.